2022
DOI: 10.1007/s10528-022-10263-y
|View full text |Cite
|
Sign up to set email alerts
|

RP11-79H23.3 Inhibits the Proliferation and Metastasis of Non-small-cell Lung Cancer Through Promoting miR-29c

Abstract: Evidences indicate that long non-coding RNAs (lncRNAs) are closely involved and contributed to tumorigenesis and cancer progression. As a novel lncRNA, RP11-79H23.3 was found to be an anti-oncogene in bladder cancer. However, the essential roles and functions of RP11-79H23.3 in non-small-cell lung cancer (NSCLC) remains to be elucidated. Here, loss of functional assay was applied to gain insights into the functions of RP11-79H23.3 on the proliferation and metastasis capabilities of A549 and H1299 cells. Meanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…miR-335-5p targets glutamate metabotropic receptor 4 (GRM4) to regulate neuronal excitability [ 47 ], and reduced glutamate levels in specific brain regions have been implicated in the pathogenesis of depression [ 48 , 49 ]; miR-335-5p is significantly increased in the plasma exosomes of people with treatment-resistant depression [ 48 ]. miR-29c is activated by the Wnt signaling pathway [ 50 , 51 ], and in the prefrontal cortex exosomes of BD patients miR-29c is significantly increased [ 30 ].…”
Section: Exosomes In the Diagnosis Of Mood Disordersmentioning
confidence: 99%
“…miR-335-5p targets glutamate metabotropic receptor 4 (GRM4) to regulate neuronal excitability [ 47 ], and reduced glutamate levels in specific brain regions have been implicated in the pathogenesis of depression [ 48 , 49 ]; miR-335-5p is significantly increased in the plasma exosomes of people with treatment-resistant depression [ 48 ]. miR-29c is activated by the Wnt signaling pathway [ 50 , 51 ], and in the prefrontal cortex exosomes of BD patients miR-29c is significantly increased [ 30 ].…”
Section: Exosomes In the Diagnosis Of Mood Disordersmentioning
confidence: 99%
“…Furthermore, multiple lncRNAs and circRNAs can regulate the Wnt/ b-catenin signaling pathway by serving as competing endogenous RNA (ceRNA) for miRNAs in LC. Liu et al showed that lncRNA RP11-79H23.3 knockdown enhanced the activity of the Wnt/b-catenin signaling pathway in NSCLC cells by sequestering miR-29c, resulting in the facilitation of LC progression (98). Yang et al revealed that circ_0017109 knockdown decreased FZD4 levels by releasing miR-671-5p, resulting in the enhancement of the Wnt/b-catenin signaling pathway and subsequent facilitation of NSCLC progression (99).…”
Section: Wnt/b-catenin Pathwaymentioning
confidence: 99%
“…Several miRNAs have been reported to regulate ovarian cancer progression by directly targeting integrin mRNAs ( Table 1 ). In particular, miR-29c is reported to target integrin alpha-6 (ITGA6), inhibiting ovarian cancer cell adhesion, migration, and invasion [ 57 ]. On the contrary, Fu et al studied the expression profile of miR-93 in ovarian cancer cells resistant to cisplatin.…”
Section: Introductionmentioning
confidence: 99%